CuO NPs dose and duration dependent modulation of instantaneous growth rate (IGR) of the earthworm D. willsi:Evidence of threshold- driven toxic response - Neha Swati Baxla; Rohit Srivastava; Manoranjan Prasad Sinha (The Bioscan, 2026)
The increasing release of copper oxide nanoparticles (CuO NPs) into terrestrial ecosystems necessitates evaluation of their sublethal effects on key soil fauna.